2013
DOI: 10.1104/pp.113.216077
|View full text |Cite
|
Sign up to set email alerts
|

The Anticipation of Danger: Microbe-Associated Molecular Pattern Perception Enhances AtPep-Triggered Oxidative Burst  

Abstract: The endogenous Arabidopsis (Arabidopsis thaliana) peptides, AtPeps, elicit an innate immune response reminiscent of patterntriggered immunity. Detection of various danger signals, including microbe-associated molecular patterns (MAMPs), leads to elevated transcription of PROPEPs, the AtPep precursors, and PEPRs, the AtPep receptors. It has been hypothesized that AtPeps are involved in enhancing pattern-triggered immunity. Following this idea, we analyzed the relationship between MAMP-and AtPep-elicited signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 38 publications
5
83
0
2
Order By: Relevance
“…However, protonation of some key residues such as PEPR1 Arg487 that forms salt bonds with the free carboxy group of AtPep1 ( Figure 3B) might contribute to this process. A number of studies suggest that AtPeps function as an amplifier of PTI [25][26][27][28], one hallmark of which is an increase in medium pH [36,37]. Although further in vivo studies are required to investigate whether and how PTI is associated with the pH-dependent PEPR1LRR recognition of AtPep1, this observation indicates that changes in pH during PTI can affect the biochemical activities of signaling molecules involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, protonation of some key residues such as PEPR1 Arg487 that forms salt bonds with the free carboxy group of AtPep1 ( Figure 3B) might contribute to this process. A number of studies suggest that AtPeps function as an amplifier of PTI [25][26][27][28], one hallmark of which is an increase in medium pH [36,37]. Although further in vivo studies are required to investigate whether and how PTI is associated with the pH-dependent PEPR1LRR recognition of AtPep1, this observation indicates that changes in pH during PTI can affect the biochemical activities of signaling molecules involved.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to FLS2 and EFR, PEPR1 stably associates with BAK1 in response to treatment with AtPeps [23,24]. A number of studies suggest that PEPR-mediated immune responses serve to amplify PTI signaling [25][26][27][28] via the JA/ET (jasmonic acid-ethylene) and SA (salicylic acid) pathways [25,28]. A more recent study suggests that PEPR1,2-mediated signaling has a critical role in coupling local and systemic immunity [29].…”
Section: Introductionmentioning
confidence: 99%
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010). Finally, it is possible to determine the redox potential of the glutathione pool in a high spatial and temporal resolution using various redox-sensitive green fluorescent proteins (for example roGFP) encoded in the test plant.…”
Section: Detection Of Rosmentioning
confidence: 99%
“…The timing of the treatments was designed to allow plant material to be collected under similar light conditions and to minimize changes in physiology. Previous work showed that for soil-grown plants, a water pretreatment of excised tissue was needed to detect an flg22-induced ROS response (Felix et al, 1999;Flury et al, 2013). However, the long water pretreatments that are typically used can mask mutant phenotypes, making long pretreatments unsuitable for assessing the basal state of some plants.…”
Section: Acd6-1 and Bth-treated Wild-type Plants Show Potentiated Rosmentioning
confidence: 99%
“…We sought to also assess the levels of these receptors under the same conditions used for the experiments in Figure 1, where we evaluated the flg22 responses of acd6-1 and which involved floating tissue on water for 4 h prior to flg22 application. This water pretreatment step was proposed to remove wounding stress resulting from excising the leaves (Flury et al, 2013). Water pretreatment for 4 h after excising leaf tissue caused increased receptor levels in total extracts of the wild type but had more modest effects on the levels in the membrane fractions (Supplemental Figure 1J).…”
Section: Acd6-1 and Bth-treated Wild-type Plants Show Potentiated Rosmentioning
confidence: 99%